CITIZEN ADOPTION AND SATISFACTION ON DIGITAL INDIA SERVICES IN GREATER CHENNAI CORPORATION - SHANKAR KUMAR S , Dr. B. JEYAPRABHA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Digital India movement was initiated to enable citizen to gain knowledge on the digital economy and society and transferring all that into a digital way and presenting the transparency of our nation electronically.The key aim is to create awareness and satisfaction among people about the digital India program across the nation. The main objective of this study is to assess the citizen adoption and satisfactionon digital India services at Greater Chennai Corporation.This research is descriptive in nature and target audience is respondent residing in Greater Chennai Corporation.The sample size of this study representing 110 Citizens of Greater Chennai Corporation. Secondly, the sampling method adopted for this study is non-probability sampling using convenience sampling methodis used for the target population. The Likert five point rating scale questions areused for collecting the data through structured questionnaire.The finding revealed that the citizenadoption and the satisfaction towards the digital India Programme at Greater Chennai Corporationwhich was highly appreciated and they felt that they were accesstowards digital India services and having the positive view on digital India programme.This result shows that digital India is potential and capable to change the face of our nation and it moves constantly towards improvement without a doubt.Future research would belike loyalty, engagement and empowerment of citizens through digital India services may also be considered for research.